2001
DOI: 10.1074/jbc.m008046200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Heparan Sulfate Proteoglycans Participate in Factor VIII Catabolism Mediated by Low Density Lipoprotein Receptor-related Protein

Abstract: Factor VIII (fVIII) 1 is an essential component of the intrinsic pathway of blood coagulation, since genetic deficiency in fVIII results in a coagulation disorder known as hemophilia A and occurs in 1 per 5000 males. In the intrinsic pathway, activated fVIII (fVIIIa) functions as a cofactor for the serine protease factor IXa, and their membrane-bound complex (Xase complex) activates factor X to factor Xa (1). Factor Xa subsequently participates in activation of prothrombin into thrombin, the key enzyme of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 62 publications
5
127
2
Order By: Relevance
“…HSPGs have been demonstrated to mediate endocytosis of ligands including lipoproteins (44). Alternatively, HSPGs might act as co-receptors of LRP-1-mediated endocytosis as proposed for thrombospondin 1 (45), tissue factor pathway inhibitor (46), amyloid-␤ (47), and factor VIII (48). However, we found that TIMP-3 endocytosis was not affected in xylosyltransferase-deficient CHO-745 cells, indicating that sulfated cell surface proteoglycans are not required for TIMP-3 endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…HSPGs have been demonstrated to mediate endocytosis of ligands including lipoproteins (44). Alternatively, HSPGs might act as co-receptors of LRP-1-mediated endocytosis as proposed for thrombospondin 1 (45), tissue factor pathway inhibitor (46), amyloid-␤ (47), and factor VIII (48). However, we found that TIMP-3 endocytosis was not affected in xylosyltransferase-deficient CHO-745 cells, indicating that sulfated cell surface proteoglycans are not required for TIMP-3 endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such affinities are unlikely to provide effective direct interactions of FVIII with both receptors in vivo, considering the concentration of FVIII in plasma (ϳ0.3 nM). For LRP, its in vivo interaction with FVIII is facilitated by cell surface heparan sulfate proteoglycans (34). Whether this type of receptors serves a similar role for LDLR is unknown.…”
Section: Factor VIII (Fviii)mentioning
confidence: 99%
“…Investigation of the molecular basis thereof has recently started. [11][12][13] It has been demonstrated that FVIII clearance is facilitated by cell surface heparan sulfate proteoglycans. 13 These are thought to act by preconcentrating ligands on the cell surface that subsequently transfer their ligands to endocytic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] It has been demonstrated that FVIII clearance is facilitated by cell surface heparan sulfate proteoglycans. 13 These are thought to act by preconcentrating ligands on the cell surface that subsequently transfer their ligands to endocytic receptors. 14 Recently, it has been demonstrated that FVIII comprises multiple binding sites that mediate the interaction with the low-density lipoprotein receptorrelated protein (LRP).…”
Section: Introductionmentioning
confidence: 99%